Game Application as A Tool for Enhancing English Learning: A Development Study - Nursyah Handayani; Lahmudin Sipahutar (International Journal of Computer and Information System (IJCIS), 2025)
The rapid advancement of digital technology has encouraged educators to explore innovative tools that enhance language learning outcomes. This study reports the development of a mobile-based English learning game application designed to improve vocabulary acquisition, reading comprehension, and learner motivation. Using a design-based research framework, the application was developed through three stages: needs analysis, prototype development, and expert evaluation. Data were collected through questionnaires, user testing, and interviews involving 35 junior high school students and three English teachers. The findings show that the game application significantly increased students’ engagement and supported improvements in targeted language competencies. Expert validation confirmed that the application met pedagogical, technical, and usability standards. This study concludes that interactive game-based applications can serve as effective supplemental tools for English learning. Suggestions for further development and recommendations for classroom implementation are also discussed.